2017
DOI: 10.1016/j.ymgme.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine in rare disease: Mechanisms of disparate effects of N -carbamyl- l -glutamate on mutant CPS1 enzymes

Abstract: This study documents the disparate therapeutic effect of N-carbamyl-L-glutamate (NCG) in the activation of two different disease-causing mutants of carbamyl phosphate synthetase 1 (CPS1). We investigated the effects of NCG on purified recombinant wild-type (WT) mouse CPS1 and its human corresponding E1034G (increased ureagenesis on NCG) and M792I (decreased ureagenesis on NCG) mutants. NCG activates WT CPS1 sub-optimally compared to NAG. Similar to NAG, NCG, in combination with MgATP, stabilizes the enzyme, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Indeed, it has been used in single cases of ornithine transcarbamylase deficiency and citrullinemia type 1 . Observations in CPS1D indicated that the deficiency must be partial to be NCG‐sensitive, and suggested that the specific mutations found in each patient can determine the degree of response to NCG . The homozygous p.(Pro1211Arg) novel mutation found in our patient is shown here to cause partial deficiency and was associated with partial susceptibility to NCG.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Indeed, it has been used in single cases of ornithine transcarbamylase deficiency and citrullinemia type 1 . Observations in CPS1D indicated that the deficiency must be partial to be NCG‐sensitive, and suggested that the specific mutations found in each patient can determine the degree of response to NCG . The homozygous p.(Pro1211Arg) novel mutation found in our patient is shown here to cause partial deficiency and was associated with partial susceptibility to NCG.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, a corollary of all the above is that potential chaperoning effects of NCG should be kept in mind because they may be crucial in determining NCG effectiveness in CPS1D. As mutation effects on CPS1 stability may not be easily predictable, and given the poor general prognosis of CPS1D, it appears reasonable to give patients a clinical trial of NCG to assess the clinical responsiveness to this orphan drug, taking due caution with monitoring for potential negative effects of NCG as observed in a single CPS1D patient …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, basic studies have shown that N-carbamyl-L-glutamate (NCG), the chemical analog of CPS1's essential activator, can improve and protect the function of mutant CPS1. Clinical studies have also shown that NCG had beneficial effects on CPS1-deficient patients with some special mutations, such as the p.Glu1034Gly mutation [3]. The treatment outcomes depends on disease severity.…”
Section: Introductionmentioning
confidence: 99%